Seedling production of coffea arabica from different cultivars in a modified hydroponic system and nursery using different containers - de Lima, Amador Eduardo; Guimarães, Rubens José; da Cunha, Samuel Henrique Braga; Castro, Elisa de Melo; de Carvalho, Alex Mendonça [UNESP]; Faria, Mauro Magalhães Leite (FapUNIFESP (SciELO), 2021)
The development of modified hydroponic cultivation has aroused interest and its use has enabled advantages in several crops, but studies for coffee are still scarce. Thus, the objective of this research was to evaluate seedling production of three Coffea arabica cultivars (Mundo Novo IAC-376-4, Catuaí IAC-62 Amarelo and MGS Paraíso 2), in a modified hydroponic system, and to compare it with the nursery production system, using plastic polyethylene tubettes and bags. Coffee seedlings in the development phase with cotyledon leaves, were cultivated in both cultivation systems. At 90 days after the implementation of the experiment, the seedlings were analyzed for growth (height, stem diameter, total number, leaf area, root area, root and shoot dry matter weight), and physiological characteristics (chlorophyll content and stomatal conductance). For the statistical analysis, a completely randomized design (CRD) was used in a factorial scheme 3 (cultivars) x 2 (containers) x 2 (cultivation systems), with four replications of ten plants per plot. The innovative production system of coffee seedlings in modified hydroponics, in combination with the use of polyethylene bags, provided greater growth of coffee seedlings with better physiological characteristics. Among the cultivars tested, MGS Paraíso 2 stood out with higher seedling growth (number of leaves, stem diameter and root and shoot dry matter weight).
Produção de mudas de diferentes cultivares de coffea arabica em sistema hidropônico modificado e viveiro utilizando diferentes recipientes
Keywords: Coffee; Modified cultivation; Seeds